Accuracy improvement in amplitude comparison‐based passive direction finding systems by adaptive squint selection. Issue 5 (1st May 2020) - Iqbal, Muhammad Faisal; Khalid, Zubair; Zahid, Muhammad; Abdullah, Asim
Abstract : The direction of arrival (DOA) is one of the most important parameters measured by electronic warfare systems. Monopulse direction finding techniques based on amplitude comparison have many advantages because of their simplicity but they generally have limited accuracy. There are many sources of error in such a system. This work focuses on improving the noise error. An algorithm is proposed for error reduction in amplitude comparison‐based direction finding systems. The algorithm, based on signal level and DOA, adaptively utilises either adjacent or alternate antennas for the DOA measurement. No additional hardware is required for the implementation of this algorithm. A prototype system is developed using spiral antennas and the performance of the proposed technique is compared against traditional ratio‐based and correlation‐based amplitude comparison schemes. Simulations and laboratory experiments show that the DOA accuracy can be improved by an average of 36 and 21% as compared to the ratio‐based and correlation‐based methods, respectively.